Revenge Porn in Criminal Law: A New Form of Cyber Bullying, Qanun Jinayah, and Other Legal Consequences - Galih Raka Siwi; Raihan Khoerunisa; Puti Priyana (IHSA Institute, 2022)
The trend of technological development coupled with the Covid-19 pandemic has made an increase in online-based forms of sexual violence crimes, especially regarding Revenge Porn. The purpose of writing this paper is to provide academic contributions and further references to the problem of revenge porn that is rampant in Indonesia. Discussion 1 and discussion 2 are studied juridically normatively with descriptive-analytical specifications. The results showed that so far the Criminal Code, Regulation on Pornography, Regulation on ITE, Regulation on Sexual Violence Crimes and Qanun Aceh can be used as a legal umbrella for revenge porn in Indonesia. Then, which various regulations regarding Revenge Porn are a form of legal liability that can be imposed on revenge porn perpetrators as part of the criminal law itself, namely providing imprisonment for confinement and also fines as a form of providing certainty, justice, and legal expediency for revenge porn in Indonesia.